Cases of Acute Renal Failure and Haemodialysis at Shree Birendra Hospital - Bajracharya, Swasti Bajra (Medical Journal of Shree Birendra Hospital, 1999)
Cases of Acute Renal Failure and Haemodialysis at Shree Birendra Hospital